2006
DOI: 10.1007/s10661-006-6548-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Trace Metal Concentrations in the Cockle, Austrovenus Stutchburyi from Otago, New Zealand

Abstract: This is the first comprehensive study of sources of variation in metal concentrations within the whole tissues of a shallow burrowing, filter-feeding intertidal clam, Austrovenus stutchburyi. Samples were collected from 12 sites in April, August, November and February in 1993-1994 in the vicinity of Otago Harbour and Peninsula, New Zealand. Total tissue trace metal concentrations (microg g(-1) dry weight) were measured in individual animals for the essential metals : Mn, Cu, Zn, Ni and the non-essential Cr usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It has been reported that the soft tissue dry weight of the mollusk Arctica islandica reached maximum values during the summer months (Swaileh 1996). Peake et al (2006) reported that the Cu tissue concentration of Austrovenus stutchburyi appeared to increase with declining the condition index. In our investigation, the condition index (soft tissue dry weight/shell Wet tissue-based data were converted to dry tissue-based data by assuming water content of 83% (Usero et al 1997) dry weight × 100) of R. philippinarum was 10.84-12.12% in August compared to 4.60-6.10% in December.…”
Section: Variations In Metal Concentrations In R Philippinarummentioning
confidence: 99%
“…It has been reported that the soft tissue dry weight of the mollusk Arctica islandica reached maximum values during the summer months (Swaileh 1996). Peake et al (2006) reported that the Cu tissue concentration of Austrovenus stutchburyi appeared to increase with declining the condition index. In our investigation, the condition index (soft tissue dry weight/shell Wet tissue-based data were converted to dry tissue-based data by assuming water content of 83% (Usero et al 1997) dry weight × 100) of R. philippinarum was 10.84-12.12% in August compared to 4.60-6.10% in December.…”
Section: Variations In Metal Concentrations In R Philippinarummentioning
confidence: 99%
“…M. galloprovincialis can be used as a sensitive indicator for the availability of trace elements in the coastal waters off Korea [301]. A study of sources of variation in element concentrations within the whole tissues of the shallow burrowing, filter-feeding intertidal clam Austrovenus stutchbury was performed [302]. Bioaccumulation of 12 heavy metals in the shells of Mytilus edulis was investigated [303].…”
Section: Studies On Animalsmentioning
confidence: 99%